A new species of Fansipaniana from Northern Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Olethreutini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2016)
Vietnam micro-moths remain poorly known, and new species are discovered year after year among the Tortricidae (Kuznetzov 1992, 2000; Razowski 2003, 2008; Heppner 2010; Heppner and Bae 2015a, b) and other families (e.g., Park et al. 2007). Razowski (2009) described the genus Fansipaniana for a single new species from the high mountains in northern Vietnam close to the border with China. Recent exploration of many areas in Vietnam has resulted in the discovery of a second species of Fansipan-iana from a lower elevation mountain range near Hanoi. The new species is from Tam Dao, one of the most well known sites in Vietnam for moth collecting.